β-catenin is selectively required for the expansion and regeneration of mature pancreatic acinar cells in mice - Matthew D. Keefe; Hui Wang; Jean-Paul De La O; Ameena Khan; Matthew A. Firpo; L. Charles Murtaugh (The Company of Biologists, 2012)
SUMMARY The size of the pancreas is determined by intrinsic factors, such as the number of progenitor cells, and by extrinsic signals that control the fate and proliferation of those progenitors. Both the exocrine and endocrine compartments of the pancreas undergo dramatic expansion after birth and are capable of at least partial regeneration following injury. Whether the expansion of these lineages relies on similar mechanisms is unknown. Although we have shown that the Wnt signaling component β-catenin is selectively required in mouse embryos for the generation of exocrine acinar cells, this protein has been ascribed various functions in the postnatal pancreas, including proliferation and regeneration of islet as well as acinar cells. To address whether β-catenin remains important for the maintenance and expansion of mature acinar cells, we have established a system to follow the behavior and fate of β-catenin-deficient cells during postnatal growth and regeneration in mice. We find that β-catenin is continuously required for the establishment and maintenance of acinar cell mass, extending from embryonic specification through juvenile and adult self-renewal and regeneration. This requirement is not shared with islet cells, which proliferate and function normally in the absence of β-catenin. These results make distinct predictions for the relative role of Wnt-β-catenin signaling in the etiology of human endocrine and exocrine disease. We suggest that loss of Wnt-β-catenin activity is unlikely to drive islet dysfunction, as occurs in type 2 diabetes, but that β-catenin is likely to promote human acinar cell proliferation following injury, and might therefore contribute to the resolution of acute or chronic pancreatitis.